DIAGENETIC FEATURES OF PALEO LAGOONAL REEF OF TACIPI AREA, SOUTH CELEBES - Andri Slamet Subandrio; Ediar Usman (BULLETIN OF THE MARINE GEOLOGY, 2011)
Limestone outcrops of the Tacipi area is an ideal carbonate platform part of Neogene East and West Sengkang Basin that are located in the south part of Sulawesi, precisely in western of Bone city. The limestones of this area, outcropping mainly on the north-south oriented hills such as Temapole, Anadara, Tamping, Lappa, etc., are the best reef example in the Tacipi area, as the reef itself, its debris and detritus can be distinguished in the field. Throughout the ridges and pinnacle in Tacipi field the limestones are predominantly homogenous boundstones on the top and detrital bioclastic packstones with local grainstones, and wackestones at the bottom. There are four major reef zonation indentified pacth reef, barrier reef, fore reef and lagoon. The extensive freshwater leaching of fossil fragments and calcareous cement give the preservation of biomouldic and vug pore spaces. Abstract Limestone outcrops of the Tacipi area is an ideal carbonate platform part of Neogene East and West Sengkang Basin that are located in the south part of Sulawesi, precisely in western of Bone city. The limestones of this area, outcropping mainly on the north-south oriented hills such as Temapole, Anadara, Tamping, Lappa, etc., are the best reef example in the Tacipi area, as the reef itself, its debris and detritus can be distinguished in the field. Throughout the ridges and pinnacle in Tacipi field the limestones are predominantly homogenous boundstones on the top and detrital bioclastic packstones with local grainstones, and wackestones at the bottom. There are four major reef zonation indentified pacth reef, barrier reef, fore reef and lagoon. The extensive freshwater leaching of fossil fragments and calcareous cement give the preservation of biomouldic and vug pore spaces.